Homalomeneae (Araceae) of Borneo XXX — Homalomena atlas [Hanneae Complex] a new species from the Rejang Basin, Sarawak - Wong, Sin Yeng; Peter C., Boyce (Firenze University Press, 2023)
Homalomena atlas is described and illustrated as a new species from the western Rejang Basin and assigned to the Hanneae Complex of the Cyrtocladon Clade, taking the complex to 12 described species on Borneo.